Employee Performance as a Function of Job Orientation and Job Design - Sales, Carol; Levanoni, Eliahu; Knoop, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
Two weaknesses in previous job design research were examined: the overuse of self-report measurements and the questionable use of Growth Need Strength as a moderator between job characteristics and employee performance. Job orientation was hypothesized to moderate the relationship between job characteristics and employee performance. Results indicated that job orientation moderated the relationship between job characteristics and quality of performance but not between job characteristics and quantity of performance, job involvement and satisfaction with work.